Undersøgelse af EmpowerMindTræning som intervention mod stress - Svenstrup, Jørgen (Psyke & Logos, 2016)
Stress is an increasing problem in Denmark with more than 12% of the population suffering from stress on a regular basis, and the interventions used to reduce stress are still a mix of remove-from-stressors strategies and coping strategies, whereas research indicates that the coping strategies are the most beneficial. This paper investigates the effect of a coping strategy to reduce stress called EmpowerMindTraining (EMT). EMT consists of a combination of mental training, originally used to improve performance and results of elite athletes using an altered state of consciousness, and a compliance concept introduced to secure the continuing use of the daily mental training during the full investigation period. The results show that EMT seems to be a beneficial intervention against stress on all levels, with good effect on a vast majority of the responders. Further investigation into the effect of EMT is suggested.